KEEFEKTIFAN PELATIHAN GURU TAHU UNTUK MENINGKATKAN TEACHER WELL-BEING PADA GURU SEKOLAH DASAR INKLUSI - Berliana, Azirna Berliana; Nugraha, Sumedi P. (JIP (Jurnal Intervensi Psikologi), 2024)
Inclusive school teachers are required to have adequate preparation to conduct optimal teaching processes for students with disabilities. Such preparations lead to work pressure and negative emotions, resulting in low teacher well-being. This study aimed to enhance the teacher well-being of inclusive elementary school teachers through the "Guru Tahu" training. The research design employed a quasi-experimental approach with a pretest and posttest control group design model. The participants were 16 inclusive elementary school teachers in Yogyakarta with low scores on the TWBS scale and basic knowledge related to students with disabilities. The results of Mann Whitney-U test indicated a significant difference with p <0,001, suggesting that the "Guru Tahu" training was effective in improving teacher well-being for teachers in inclusive elementary school "X" and "Y" in Yogyakarta.